ROLE AND IMPACT OF WOMEN ENTREPRENEURS FOR THE RURAL DEVELOPMENT IN JAMMU, J&K, INDIA AND ITS MAJOR SOCIO-ECONOMIC FACTORS - Kour, Gurmeet; Yadav, Urmila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this paper we explore the role and impact of women entrepreneurs for the rural development in jammu, j&K, India and its major socio-economic factors. “Promoting an alternative job scenario in rural communities is the role of entrepreneurship. Economic capital, manpower, supplies, money, machines and management are the factors driving the rural ownership of entrepreneurs. Furthermore, the variables depend on the elements of caste, profession, salaries, expertise, talents and other abilities. Social capital, the literature review portion, was described from the point of view of several thinkers. In sustainable urban development, there are perceived to be influential factors and the associated problems are planned accordingly. It was found that almost 50 percent of the Indian population is female, but male dominance is witnessed in the business domain, including banking, trade and industry. The proportion of female entrepreneurs in India is as low as 7%, led by the Gujarat and Maharashtra states in the charts. Given the ability of women , it is critical that necessary steps through entrepreneurial platforms are guided towards their economic empowerment. In addition to the underlying stereotype that women are weak and indecisive, in their attempts to grow their businesses such as health issues, social factors, cultural factors, casting factors, economic factors, political factors, women entrepreneurs face various obstacles. Issues affecting female entrepreneurs were examined in rural areas and found that most female entrepreneurs were ranked as lacking good leadership. Their level of leadership in order to become a successful entrepreneur was not as strong as necessary. Enterprises are facing difficulties with regard to inadequate funding and limited capital funds. Only a very negligible percentage decrease was not a major improvement. The author may therefore suggest that. A strategy for Women Entrepreneurs focus on empowerment by training and capacity building projects should be built by government.” If our educational institutions, colleges and organisations join this resolution with increasing emphasis on women's business education, the future will see more women entrepreneurs. Without proper planning, rural entrepreneurship won't be built. It is therefore necessary to provide training for rural women to enhance their entrepreneurial skills and set out their paths to emancipation.